Bioclimatic characterization of the world areas of Endemism identified for Mammals - Escalante, Tania; Guevara-Juárez, Linda M.; Mercado-Gómez, Jorge D. (Zootaxa, 2019)
Areas of endemism (AoE) are identified by the congruence of two or more geographic distribution areas. They represent patterns of distribution resulting from ecological and evolutionary processes and constitute the basic units of biogeographic regionalizations; however, they are not usually environmentally characterized. The 54 world areas of endemism identified for terrestrial mammals were bioclimatically characterized by climate and biome type, using two diversity indices. The climatic characterization shows that tropical climates, mainly Aw (equatorial savannah with dry winter) and Af (equatorial rainforest, fully humid) were the most frequent; included in 32 areas of endemism. The most frequent biomes were the tropical and subtropical moist broadleaf forests, which grow at low altitudes. Most of the endemic taxa are located in lowlands, frequently from 0 to 1,000 m of altitude. Our results suggest that AoE are concentrated in tropical latitudes; however, we did not find any correlation between the homogeneity of the climate or the biome and the number of endemic taxa within each AoE. Therefore, we suggest that these AoE could have been mainly shaped by tectonic events, combined with environmental influence.